Effectiveness of Spiritual Learning on Anxiety Patients of Pre Prefects Cesarean - Heni Frilasari; heri triwibowo (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Anxiety can affect the condition of pregnant women. Also, it causes increased heart rate and systolic blood pressure. The psychological responses make individuals withdraw and reduce involvement with others. cognitive responses unable to pay attention decreased concentration. And effective response causes confusion and excessive suspicion. Impact of anxiety can be minimized by doing spiritual guidance to lower anxiety levels. The purpose of the research was to know the influence of spiritual guidance on the level of anxiety in patients pre Sectio Caesar in RSI Sakinah Mojokerto. This research used analytic design. The population was all pre-operative patients in SSI surgery Sakinah Mojokerto, and samples taken with consecutive sampling type. The instruments used are spiritual guidance and anxiety materials using HARS questionnaires. The result of research by using Wilcoxon signed rank test, got Ï value equal to 0.000 <0,05, then H0 rejected, mean there is the influence of spiritual guidance to pre patient's anxiety level in surgery room of Hasyim As'ary RSI Sakinah Mojokerto. Spiritual guidance is one means of good therapeutic communication to improve the mechanism of coping and individual relaxation because it is spiritual guidance should be used as a communication of health workers in midwifery care.